Development assistance, strategic interests, and the China factor in Japan's role in ASEAN integration - Yoshimatsu, Hidetaka (Animo Repository, 2010)
In this article, we have examined how Japan has supported ASEAN's economic integration through ODA and other diplomatic measures, and showed how Japan's engagements in ASEAN economic integration evolved over time. In addressing these issues, we took into account the growing influence of China's ascent in Southeast Asia, and assumed that Japan's China policy of mixed accommodation and balance became explicit in Japan's ASEAN policy. The pronouncement of support for ASEAN integration, disbursement of aid to the region, forging of bilateral and regional FTAs/EPAs with ASEAN, and its recent initiatives and proactive involvement in the Mekong regional development are indicative of Japan's reactive posture on China's growing influence in the region. Japanese diplomatic initiatives in ASEAN are intended, in part, to accommodate and balance China's increasing prominence in Southeast Asia. This explains the simultaneous existence of competitive and cooperative initiatives of the two countries with ASEAN. © 2010 Cambridge University Press.